2009
DOI: 10.1007/s12257-009-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions and medium components for the production of mycelial biomass and exo-polysaccharides with Cordyceps militaris in liquid culture

Abstract: Both crude exo-biopolymers and mycelial biomass, produced by liquid culture of `çêÇóÅÉéë species, are believed to possess several potential health benefits. As a result of its known biological activities, `çêÇóÅÉéë=ãáäáí~êáë has been extensively characterized in regards to potential medicinal applications. However, optimized liquid culture conditions for enhanced polysaccharide productivity have yet to be developed, which is a necessary step for industrial applications. Therefore, in this study, the liquid cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The least mycelia yield was produced with fructose, xylose and sorbitol in strains 218, 339 and 340 respectively. The result from the study is consistent with other work that reported starch and mannose as being widely utilized by many basidiomycetes [10] [18]. Starch utilization is possible because some basidiomycetes synthesize effective amylolytic enzymes for hydrolysis of starch.…”
Section: Utilization Of Different Carbon Sourcessupporting
confidence: 92%
See 1 more Smart Citation
“…The least mycelia yield was produced with fructose, xylose and sorbitol in strains 218, 339 and 340 respectively. The result from the study is consistent with other work that reported starch and mannose as being widely utilized by many basidiomycetes [10] [18]. Starch utilization is possible because some basidiomycetes synthesize effective amylolytic enzymes for hydrolysis of starch.…”
Section: Utilization Of Different Carbon Sourcessupporting
confidence: 92%
“…Therefore, it is not surprising that the strains studied produced high biomass with mannose. Similar response is seen in other basidiomycetes including Cordycceps militaris [18], Pleurotus tuber-regium [20], and Grifola frondosa [21]. Intermediate utilization of mannitol by strain 218 and other basidiomycetes is associated with substrate oxidation or dehydrogenase enzyme activity [22].…”
Section: Utilization Of Different Carbon Sourcesmentioning
confidence: 58%
“…These optimization methods involve three major steps: performing statistically designed experiments, estimating coefficients in a mathematical model to predict the response and checking the adequacy of the model [11,12]. RSM has been widely used in the optimization of the fermentation process such as media components for the production of enzyme [13,14], exopolysaccharides [15], other metabolites [16][17][18], biomass [19], and for predicting the growth rate of Bacillus cereus [20]. RSM is an effective tool for optimizing the process [21] when many factors and interactions affect the desired response.…”
Section: Introductionmentioning
confidence: 99%
“…After 11 days of cultivation, the culture broth was centrifuged at 5000 rpm for 20 min. Precipitated mycelia were washed three times with distilled water, and then freeze-dried (Kwon, Lee, Shin, Lee, & Hong, 2009). Dialysis tubing cellulose membranes, DEAE cellulose, Sepharose CL-6B, standard dextrans, lipopolysaccharide (LPS, Escherichia coli 0111:B4), laminarin, curdlan, and Congo red were purchased from Sigma Chemical Co. (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%